2018
DOI: 10.5099/aj180400189
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Levels of Parathyroid Hormone, Oestrogen and Selected Bone Minerals in Menopausal Women

Abstract: Menopause is associated with various physiological and biochemical changes that have effects on bone minerals and their metabolism. There have been a lot of complaints about bone pains and bone related problems especially among middle aged women. Thus, the work was designed to assess and compare the levels of parathyroid hormone (PTH), oestrogen and selected bone minerals (calcium and phosphate) in preand post-menopausal women. A total of one hundred subjects were investigated. They comprised fifty premenopaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
1
2
1
Order By: Relevance
“…PTH levels were higher in women aged ≥ 75 years even though no statistically significant association between PTH and age was found in the study. This finding does not support those of previous studies that reported increasing PTH levels with age [16,17]. Indeed, Oluboyo and colleagues found significantly increased levels of PTH along with calcium and phosphorus among Nigerian postmenopausal women [17].…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…PTH levels were higher in women aged ≥ 75 years even though no statistically significant association between PTH and age was found in the study. This finding does not support those of previous studies that reported increasing PTH levels with age [16,17]. Indeed, Oluboyo and colleagues found significantly increased levels of PTH along with calcium and phosphorus among Nigerian postmenopausal women [17].…”
Section: Discussioncontrasting
confidence: 65%
“…This finding does not support those of previous studies that reported increasing PTH levels with age [16,17]. Indeed, Oluboyo and colleagues found significantly increased levels of PTH along with calcium and phosphorus among Nigerian postmenopausal women [17].…”
Section: Discussioncontrasting
confidence: 65%
“…E. Los resultados son contrarios a los encontrados en otros estudios que muestran que la aplicación de Se y Vit. E estimulan un mayor libido y mayor desempeño reproductivo en el macho (Ali et al 2009, Oluboyo et al 2012, Gamal et al 2013. Una probable causa, que pudo afectar el desempeño reproductivo de los carneros pudo deberse al intervalo de tratamiento y dosis utilizadas en nuestro tratamiento.…”
Section: Resultados Y Discusiónunclassified
“…28 Subsequently, calcium is liberated from the bone when the parathyroid hormone levels are high, resulting in higher calcium blood levels. 29,30 Fig. 1 illustrates how menopause leads to bone issues.…”
Section: Menopause In Womenmentioning
confidence: 99%